Penerapan Model Make a Match dalam Meningkatkan Keaktifan Belajar Peserta Didik di SMPN 57 Palembang - Saputra, Mejika Adi; Alfiandra, Alfiandra; Muniarti, Sepertia Rita (Institut Agama Islam Negeri Ponorogo, 2023)
Based on the results of observation, reflection and evaluation of the Pancasila and Citizenship Education subjects in class IX.2 for the 2022/2023 school year, it was identified that in the learning process students' activeness in participating in learning was not very good. This condition is marked when the learning activities of students are still not optimal. This study aims to increase student learning activeness with the application of Make A Match learning media. This type of research is classroom action research (PTK) through the stages of 3 cycles. The research subjects were 30 students with a total of 15 male students and 15 female students in class IX.2. Learning activities by applying the Make A Match learning model. The results showed that the application of the Make A Match cooperative learning model had been carried out very well. The active learning of students obtained from the results of observations is in the high category with a percentage of 77.00% who have reached the research target. Based on the results of this study, it can be concluded that the Make A Match learning model is proven capable and effective in the process of increasing student learning activity.ABSTRAKBerdasarkan hasil obsevasi, refleksi dan evaluasi mata pelajaran Pendidikan Pancasila dan Kewarganegaran di kelas IX.2 tahun ajaran 2022/2023 diidentifikasi dalam proses pembelajaran keaktifan peserta didik dalam mengikuti pembelajaran belum begitu baik. Kondisi ini ditandai saat kegiatan pembelajaran keaaktifan peserta didik masih belum maksimal. Penelitian ini bertujuan untuk meningkatkan keaktifan belajar peserta didik dengan penerapan media pembelajaran Make A Match. Jenis penelitian ini adalah penelitian tindakan kelas (PTK) melalui tahapan 3 siklus. Subjek penelitian adalah 30 orang peserta didik dengan jumlah 15 orang peserta didik laki-laki dan 15 orang peserta didik perempuan kelas IX.2. Kegiatan pembelajaran dengan menerapkan model pembelajaran Make A Match. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran kooperatif tipe Make A Match telah dilaksanakan dengan sangat baik. Keaktifan belajar peserta didik yang diperoleh dari hasil observasi berada pada kategori tinggi dengan persentase 77,00% yang telah mencapai target penelitian. Berdasarkan hasil penelitian tersebut, dapat disimpulkan bahwa model pembelajaran Make A Match terbukti mampu dan efektif dalam proses meningkatkan keaktifan belajar peserta didik.